Emerging conceptions of work, management and the labor market - Vallas, Steven P. (Steven Peter), 1951- (Bingley, U.K. : Emerald Publishing Limited, 2017)
Economic institutions are undergoing radical transformations, and with these has come a reconfiguration of labor market institutions, managerial conceptions of work, and the nature of authority and control over employees as well. Yet many of these changes remain poorly understood. This volume provides a sampling of state-of-the art theory and research in the field, and addresses a wide array of questions that are vital for managers, policy makers, labor unions, and employees themselves. How has new technology changed the job search process? How has the Great Recession affected racial boundaries within the labor market? What forms of managerial thinking underlie the proliferation of downsizing as a strategic practice? How have employees responded to labor market uncertainty? What shifts are unfolding within particular sectors, such as finance or health care? And how have norms been mobilized as a source of control over the performance of service work? By addressing these and other questions, this volume points the way forward for social scientific views of work and labor markets as pivotal institutions within contemporary societies.
Prelims -- Linkedin or linkedout? how social networking sites are reshaping the labor market -- Dealing with downsizing : new organizational careers in financial services after the great recession -- Neo-normative control and value discretion in interactive service work : a case study -- Engineering medicine : the deployment of lean production in healthcare -- Doing more with less : intensive care and the logic of flexible teamwork -- Race, recession, and social closure in the low-wage labor market : experimental and observational evidence -- Workforce downsizing and shareholder value orientation among executive managers at large U.S. firms -- About the editor -- Index.
Includes bibliographical references and index.
Print version record
Keywords: Management; Labor market; Social Science -- Sociology -- General; Sociology